A Learning Organization approach for Knowledge Management at Jupiter Design. - Jones, Timothy John (2006)
This report has been carried out by a student studying for the degree of a Masters in Business Administration at Nottingham University Business School. The focus of the report is to suggest a knowledge management framework for the client Jupiter Design Limited. Jupiter has experienced considerable success and growth over recent years, evolving from a relatively small but well respected design agency into one of the largest agencies operating outside of London. Due to an expanding client base and increased pressure from customers Jupiter is looking into a way of improving customer relationships, a framework of knowledge management has been suggested to support a change in the companies approach to Customer Relationship Management (CRM). A three stage methodology was adopted for this report. Stage one involved interviewing managers from Jupiter. Stage two was a literature review of information published in books, journals and websites pertaining to the topics of knowledge management and organizational learning. Stage three involved an analysis of both the literature review and the Jupiter interviews, followed by a discussion on how the analysis results could benefit Jupiter's knowledge management. A number of key issues were discovered that could potential act as blockages to knowledge management and well identified as the main address to be addressed. These were; culture, time, reward and recognition, group knowledge and the way in which mistakes are handled and help is sought within Jupiter. The framework suggested in order to overcome these issues was a model of becoming a learning organization skilled at creating, acquiring, and transferring knowledge, and at adapting its common practices to reflect new knowledge and insights. The recommended framework suggests an 11 step process designed to combat issues, these include; committing to becoming a learning organization, identifying a knowledge manager and key knowledge workers, creating a new culture, imprinting learning within all business departments, motivating staff based on their contribution to the entire company in addition to their day-to-day duties, demonstrating managers commitment to becoming a learning organization, defining a new problem solving method, setting aside time for knowledge sharing and learning, designing a relevant CRM system and finally learning more about becoming a learning organization. Should Jupiter choose to act upon these recommendations it is expected that knowledge management and in turn customer relationships will be greatly improved.